Law in transition : human rights, development and transitional justice / edited by Ruth Buchanan and Peer Zumbansen. - Buchanan, Ruth Margaret; Zumbansen, Peer; Buchanan, Ruth Margaret; Zumbansen, Peer, 1966-; Zumbansen, Peer, 1966- (Osgoode readers, 2014)
Law has become the vehicle by which countries in the 'developing world', including post-conflict states or states undergoing constitutional transformation, must steer the course of social and economic, legal and political change. Legal mechanisms, in particular, the instruments as well as concepts of human rights, play an increasingly central role in the discourses and practices of both development and transitional justice. These developments can be seen as part of a tendency towards convergence within the wider set of discourses and practices in global governance. While this process of convergence of formerly distinct normative and conceptual fields of theory and practice has been both celebrated and critiqued at the level of theory, the present collection provides, through a series of studies drawn from a variety of contexts in which human rights advocacy and transitional justice initiatives are colliding with development projects, programmes and objectives, a more nuanced and critical account of contemporary developments. The book includes essays by many of the leading experts writing at the intersection of development, rights and transitional justice studies. Notwithstanding the theoretical and practical challenges presented by the complex interaction of these fields, the premise of the book is that it is only through engagement and dialogue among hitherto distinct fields of scholarship and practice that a better understanding of the institutional and normative issues arising in contemporary law and development and transitional justice contexts will be possible.--